Penerapan Media Video Tutorial untuk Meningkatkan Hasil Belajar Peserta Didik Kelas IX SMP IT Al-Biruni Mandiri Karantina - Rifky M Fahrezy S; Sitti Rahma Yunus; Salma Samputri (Universitas Negeri Makassar, 2025)
This study aims to determine: (1) the level of learning outcomes of grade IX students of SMP IT Al-Biruni Mandiri Karantina before the application of video tutorial media, (2) the level of learning outcomes of grade IX students of SMP IT Al-Biruni Mandiri Karantina after the application of video tutorial media, (3) the increase in learning outcomes of grade IX students of SMP IT Al-Biruni Mandiri Karantina after the application of video tutorial media, (4) significant differences in learning outcomes of grade IX students of SMP IT Al-Biruni Mandiri Karantina before and after the application of video tutorial media. This research is a pre-experiment research with One Group Pretest-Posttest Design. The population of this study were all 9th grade students of SMP IT Al-Biruni Mandiri Karantina, totaling 46 students. The sample of this study was selected using purposive sampling technique with a total of 23 students. The instrument in this study was a multiple choice test question. Data analysis techniques are descriptive and inferential. The results of this study can be concluded: (1) the initial ability of students' learning outcomes before the application of video tutorials in learning obtained an average value of 45.22 with a low category, (2) the ability of students' learning outcomes after the application of video tutorials in learning obtained an average value of 74.78 with a high category, (3) the increase in students' learning outcomes after the application of video tutorials in learning obtained N-Gain 0.53 with a medium category, and (4) there is a significant difference in the learning outcomes of students in class IX SMP IT Al-Biruni Mandiri Karantina before and after the application of video tutorial media.